Digital Storytelling in Advertising: Analysis of Health Advertisements in Nigeria - Andepam, Mary Dauda; Ugondo, Peter Iorper (Darul Yasin Al Sys, 2024)
This paper examines the role of digital storytelling in health advertising within Nigeria, focusing on how this narrative technique influences public health awareness and behaviour. Utilizing a mixed-methods approach to analyze various health advertisements across digital platforms, evaluating their effectiveness in engaging audiences and conveying critical health messages. The study explores the elements of digital storytelling such as narrative structure, visual content, and interactivity and their impact on audience perception and engagement. Findings suggest that digital storytelling significantly enhances the relatability and memorability of health messages, leading to increased awareness and behavioural change. The paper also discusses the challenges and opportunities faced by health advertisers in Nigeria's digital landscape, providing insights into best practices for crafting compelling health campaigns. The study also selected a few notable case studies of digital health campaigns that have utilized digital storytelling effectively to provide detailed examples of successful digital health advertising campaigns in Nigeria.